Moana (Pacific) Expressions of Design: Setting the Conditions for Intergenerational inquiries through Learning and Creative Practice - Withers, Sonya Elspeth; Harper-Siolo, Charlotte; Hāmuera Dunstall, Samuel; Vaima’a, Pelerose; Gibbs, Kristina; Te’o-Faumuina, Alexander (Art/Research International, 2024)
This article is a reflection on an attempt to create a space of flux through the concepts of positionality, vā and talanoa within the design academy. This was presented as an academic course, originally intended to address a gap in established learning, and to make space for intergenerational knowledge systems that were originally being shared outside of the studio (shared at the knee, through office hours, and in passing conversations). This sharing led to key questions regarding how we (re)craft our ways through our practices and what cultural conditions are needed to enable safe design and cultural production. Five students enrolled in the course and are featured as co-authors in this article. They whakapapa as Tangata whenua (Māori, people of the land) or Tagata o le Moana (specifically Sāmoan). They are enrolled in a range of design disciplines such as spatial design, fashion design, and concept design. Classes were held once a week over a 12- week semester period. These in-person classes involved reflecting and re-presenting our positional contexts, a sharing and setting of kai, hikoi to gallery exhibitions featuring Māori and Pacific art practitioners at an institutional level and a community level, alongside the sharing of scholarship developed on the concepts of vā and talanoa, while coming back to ourselves and our familial, generational social settings.